Determinants of weight loss success utilizing a meal replacement plan and/or exercise, in overweight and obese adults with asthma. Issue 2 (3rd November 2014) - Scott, Hayley A.; Gibson, Peter G.; Garg, Manohar L.; Pretto, Jeffrey J.; Morgan, Philip J.; Callister, Robin; Wood, Lisa G.
Abstract Background and objective While weight loss has been shown to reduce obesity‐related comorbidity, many weight loss treatments fail. Factors that enhance weight loss success are unknown, particularly in those with asthma. The aim of the study was to identify patient characteristics that predict weight loss success in adults with asthma. Methods Baseline and change in asthma characteristics and eating behaviours were investigated for relationships with weight loss and fat loss using multiple linear regression, in 38 overweight and obese adults with asthma randomized to dietary, exercise or combined interventions targeting weight loss for 10 weeks. Results Mean ± standard deviation weight loss was 6.6 ± 5.1 kg. Greater %weight loss and %fat loss was achieved in those with poorer asthma‐related quality of life at baseline ((rs = 0.398, P = 0.015) and (rs = 0.455, P = 0.005) respectively), with 1.7% greater absolute weight loss at week 10 corresponding to each one unit reduction in the asthma‐related quality of life score at baseline. Furthermore, a lower baseline forced expiratory volume in 1 s/forced vital capacity correlated with greater weight loss (rs = 0.398, P = 0.015). Male sex was associated with a 3.6 kg greater weight loss (P = 0.087). Reducing emotional eating during the programme was associated with greater weight loss in women (rs = 0.576, P = 0.010). Conclusions This study demonstrates that individuals with more severe asthma at baseline are more successful in achieving weight loss, which could be a consequence of greater motivation and could be used as a motivational tool within the clinical setting. Gender tailoring of weight loss programmes may be useful to enhance weight loss success. Future studies are urgently needed to establish predictors of long‐term weight loss maintenance in those with asthma.